2021
DOI: 10.2196/20892
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Using Mobile Technology to Improve Cognitive and Social Skills Among Individuals With Autism Spectrum Disorder: Systematic Literature Review

Abstract: Background Mobile technology has become a necessity in the lives of people in many countries. Its characteristics and advantages also make it a potential medium of intervention for people with autism spectrum disorder (ASD). Objective The objective of this review was to evaluate previous evidence, obtained in randomized controlled trials (RCTs), on the effectiveness of using mobile devices as the medium of intervention targeting social and cognitive ski… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The results of the study showed that over a long period, social behavior in children with autism can become more integrated. Findings on the effectiveness of these tools are also confirmed in the study by Leung et al (2021) to investigate the effectiveness of their use in combating cognitive and social difficulties, reviewing the literature since 2000 by incorporating only randomized trial research. The results revealed that handheld mobile devices may be a promising tool for providing interventions for people with ASD.…”
Section: Mobile and Tablet Appsmentioning
confidence: 72%
“…The results of the study showed that over a long period, social behavior in children with autism can become more integrated. Findings on the effectiveness of these tools are also confirmed in the study by Leung et al (2021) to investigate the effectiveness of their use in combating cognitive and social difficulties, reviewing the literature since 2000 by incorporating only randomized trial research. The results revealed that handheld mobile devices may be a promising tool for providing interventions for people with ASD.…”
Section: Mobile and Tablet Appsmentioning
confidence: 72%
“…[ 16 , 17 ] Autism is a complex neurodevelopmental condition with multifaceted genetic and environmental factors at play. [ 18 ] While some studies have explored potential associations between screen time and neurodevelopmental disorders including autism, results have been inconclusive and often subject to methodological limitations. [ 19 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Таким образом, становится очевидно, что использование компьютерно-опосредованных способов общения может быть весьма полезно для развития речевых и коммуникативных навыков у подростков с РАС, однако это требует разработки качественных обучающих программ, а также способов плавной интеграции и сопровождения на начальных этапах взаимодействия с веб-средой [7].…”
Section: Building Communicative and Social Skills In An Adolescent Wi...unclassified